Material Penyusun dan Formula Campuran Beton untuk Produk PCI Girder - Brigitha rasendriya; Baskoro Abdi Praja (Seminar Nasional Penelitian dan Abdimas, 2024)
Abstract — Concrete is a composite building material made from fine aggregate (sand), coarse aggregate (split), cement as a binder, water, concrete admixtures, and additional admixtures such as fly ash, used as needed. Material testing on concrete is divided into two categories: fine aggregate testing and coarse aggregate testing. Fine aggregate testing includes mud content, organic content, fine modulus, unit weight, specific gravity, and absorption rate. Meanwhile, coarse aggregate testing includes mud content, grading to determine coarseness, unit weight, specific gravity, and absorption rate. The purpose of this study is to determine the impact of using fly ash on the constituent materials and concrete mix formulas for PCI Girder products. SNI method is used for the Job Mix Formula (JMF) mixture in this research. The effectiveness of concrete is measured by the ability of the mix to achieve or exceed the specified strength target. In this context, Trial Mix 1 is superior because it achieves higher strength. However, in terms of cost efficiency, Trial Mix 2 is more economical and sustainable, although it has lower strength but still meets the design target. Trial Mix 2 is considered more efficient overall because it meets the strength target at a lower cost and promotes the use of more sustainable materials.